Adjusting the Knox test by accounting for spatio-temporal crime risk heterogeneity to analyse near-repeats - Briz-Redón, Álvaro (European journal of criminology, 2022)
The near-repeat phenomenon usually occurs with any crime. Hence, to implement preventive measures, it is of great interest to figure out at which spatio-temporal scale crimes are more likely to be repeated by offenders. The Knox test is the most used statistical tool for evaluating the presence of the near-repeat phenomenon given a dataset of crimes that are located in space and time. The classic version of this test assumes that crime risk is homogeneous in both space and time, although this assumption rarely holds in reality. Therefore, the main goal of this article is to highlight the necessity of adjusting the standard version of the Knox test, including spatial and temporal effects that allow for the consideration of crime risk heterogeneity. In this regard, a methodology that has already been proposed for addressing this issue is described and adapted. This methodology is then put into practice through a dataset of burglaries recorded in the city of Valencia (Spain) in 2016 and 2017. The results yielded by both versions (standard and adjusted) of the Knox test confirm that the near-repeat phenomenon took place for the burglaries that occurred in Valencia during the period under investigation. However, using the adjusted version of the Knox test leads to a reduction in the number of spatio-temporal intervals that are declared as statistically significant. This fact should be born in mind before making decisions on preventive measures.